Multi-objective optimization of intermittent operation schemes of thermally activated building systems using grey relational analysis: A case study - Xuemin Sui; Lixuezi Huang; Bing Han; Jian Yan; Senfeng Yu (Case Studies in Thermal Engineering, 2023)
The thermal storage of thermally activated building systems (TABS) demonstrates the advantages of intermittent operation, however, the existing studies rarely compared different intermittent schemes to determine the optimal one. Therefore, this study presented a case study on the multi-objective optimization of intermittent operation schemes of a TABS system equipped in a typical residential building in Xi'an. Three objectives including thermal comfort, energy conservation and economic efficiency were balanced. The comparison of the 6-h, 8-h, 12-h, and 24-h cooling durations were presented. The optimal cooling duration was determined, which further optimized the cooling time distribution, and the effects of different time-of-use (TOU) electricity prices were analyzed. The results show the 8-h cooling duration is the optimal one. When the 8-h duration is designed such that to include five cooling time distributions (i.e., 8-h daytime cooling, 8-h nighttime cooling, 2-h cooling + 1-h intermittence, 1-h cooling + 1-h intermittence, and 30-min cooling + 30-min intermittence), it is found that the optimal cooling time distribution under the TOU electricity price of Xi'an is the 1-h cooling + 1-h intermittence. In addition, the TOU electricity price greatly affect determining the optimal scheme. The results can provide references for the operation of TABS.